ON PRINCIPLES AND OBJECTIVITY - Wolfgang Baatz (Ochrona Dziedzictwa Kulturowego)
The character of conservation has changed since the idea of preserving the physical remnants of history became important. Principles derived from this beginning and later on form the basis of what conservation ethics intend today. These principles were never rigid though - yet when it comes to conflict they should be transparent and precise in order to avoid the impression of arbitrariness. Developments continue, and the question where the power of decision should lie is more and more being discussed.